Change in Vertical Relationship of Upper Incisors and Lip Following Anterior Retration in Adult with the Combination Edgewise Technique - Hossein Zadeh - NikT; Hosseini Zadeh SM (Tehran University of Medical Sciences, 1999)
: One of the main aspects of orthodontic treatments is hard and soft tissue changes and their effects on patients"nappearance."nFixed orthodontic treatment with extraction of upper first premolars to camulfalge of ci II malocclusion is very common,"nhowever there is not sufficient studies about lip and incisors changes after this procedure. For evaluating of vertical changes"nof upper, lip and incisors following retraction of upper incisors, fifteen adult Iranian patients aged 15 to 24 years who"nsought treatment for their CI II DI malocclusion were treated. Standard edgewise technique(0.018") following extraction of"nfour first premolars were used."nA cephaiometric study was undertaken to determine the vertical change in upper incisors and upper lip. For this"nevaluation, thirty linear and angular measurements were utilized."nResults show that: _"n1- The upper incisors were intruded (X=0.83mm)."n2- The upper lip length was increased(X~1.2mm)."n3- The occlusal plane, rotated upward (Anteinclination)."n4- The palatal plane rotated downward and backward (Retroinclination)."nThis study shows that the standard edgwise appliance has the capacity of reduction of incisor protrusion significantly"nwithout extruding them.